Acute symptomatic seizures in term neonates: Etiologies and treatments. Issue 3 (June 2018) - Soul, Janet S.
Abstract: Acute symptomatic seizures caused by either diffuse or focal perinatal hypoxic–ischemic insults and intracranial hemorrhage in term newborns make up the large majority of all neonatal seizures. Acute seizures are one of the most common neurological disorders in term newborns who require admission to the neonatal intensive care unit. Despite elucidation of seizure pathogenesis in this population using animal models, treatment is limited by a lack of good evidence-based guidelines because of a paucity of rigorously conducted clinical trials or prospective studies in human newborns. A result of this knowledge gap is that management, particularly drug choice, is guided by clinical experience rather than by data informing drug efficacy and safety. This review summarizes the common etiologies and pathogenesis of acute symptomatic seizures, and the current data informing their treatment, including potential novel drugs, together with a suggested treatment algorithm.